Community health resource project: highlighting One Health resources across rural Georgia to build healthier communities - Jules, Tanya E.; Mercer, Megan O.; Schwind, Jessica S.; LaRose-Walthour, Patricia; Drey, Jennifer L.; Johns, Jill; Tremblay, Michelle N. (Frontiers in Public Health, 2025)
Public health professionals frequently engage with residents of rural Georgia to conduct needs-based initiatives, which aim to identify deficiencies and shortcomings in community health. However, this process can exacerbate existing stereotypes and lead community members to feel a sense of despair in their own communities. The Community Health Resource Project (CHRP) offers a counterbalance through a strengths-based approach by highlighting animal, plant, human, and environmental resources, or “One Health” assets, that currently exist in the community. CHRP begins by analyzing publicly available county-level data to gain an initial understanding of the health landscape before proceeding to the field. Next, the team engages in Participatory Asset Mapping (PAM) to gather community-driven qualitative insights on existing One Health assets in participating rural or underserved counties. Data gathered from community engagement strategies inform the development of comprehensive county-specific asset maps and reports. This paper describes the methods of applying a strengths-based approach to highlight community One Health-related assets. These strategies can be a valuable tool for developing targeted workforce development efforts in resource-limited counties for the benefit of all species.